Reconstructing the Validity of Marriage Contracts in the Digital Era: Jasser Auda’s Maqâṣid al-Syarîʿah Perspective - Risalan Basri Harahap; Kaniya Amirah Barkah Daulay; Ahmad Dabith Mubarak HSB (Madania: Jurnal Kajian Keislaman, 2025)
The development of digital technology has influenced the practice of Islamic family law, including the emergence of marriage contracts through digital media which have caused debates about its validity because classical munakahat jurisprudence requires the contract to take place in a physical assembly with the fulfillment of the marriage principles and conditions. This research aims to reconstruct the concept of the validity of marriage contracts in the digital era using the perspective of maqâṣid al-syarîʿah Jasser Auda which emphasizes a systematic, multidimensional, and goal-oriented approach to sharia. The method used is normative legal research with a conceptual and philosophical approach through qualitative analysis of primary, secondary, and tertiary sources related to munakahat jurisprudence and the theory of maqâṣid Jasser Auda. The results of the study show that the validity of digital marriage contracts cannot be assessed textually-formally alone, but must be seen from the fulfillment of the purpose of sharia, so that the concept of ittiḥâd al-majlîs can be reconstructed as a unity of time and purpose, not just a unity of physical places. A digital marriage contract can be considered valid as long as it fulfills the principles and conditions of marriage, guarantees the clarity of the qabul ijab, and protects the main maqâṣid such as ḥifẓ al-dîn and ḥifẓ al-nasl. Perkembangan teknologi digital telah memengaruhi praktik hukum keluarga Islam, termasuk munculnya akad nikah melalui media digital yang menimbulkan perdebatan mengenai keabsahannya karena fikih munakahat klasik mensyaratkan akad berlangsung dalam satu majelis fisik dengan terpenuhinya rukun dan syarat nikah. Penelitian ini bertujuan merekonstruksi konsep keabsahan akad nikah di era digital menggunakan perspektif Maqâṣid al-syarîʿah Jasser Auda yang menekankan pendekatan sistem, multidimensional, dan berorientasi pada tujuan syariat. Metode yang digunakan adalah penelitian hukum normatif dengan pendekatan konseptual dan filosofis melalui analisis kualitatif terhadap sumber primer, sekunder, dan tersier terkait fikih munakahat serta teori maqâṣid Jasser Auda. Hasil penelitian menunjukkan bahwa keabsahan akad nikah digital tidak dapat dinilai secara tekstual-formal semata, melainkan harus dilihat dari terpenuhinya tujuan syariat, sehingga konsep ittiḥâd al-majlîs  dapat direkonstruksi sebagai kesatuan waktu dan tujuan, bukan semata kesatuan tempat fisik. Akad nikah digital dapat dinilai sah sepanjang memenuhi rukun dan syarat nikah, menjamin kejelasan ijab kabul, serta melindungi maqâṣid utama seperti ḥifẓ al-dîn dan ḥifẓ al-nasl.